Aseptic Technology for Cryoprotectant-Free Vitrification of Human Spermatozoa by Direct Dropping into Clean Liquid Air: Apoptosis, Necrosis, Motility, and Viability. (25th January 2020) - Wang, Mengying; Isachenko, Evgenia; Todorov, Plamen; Rahimi, Gohar; Mallmann, Peter; Katkov, Igor I.; Isachenko, Vladimir
Abstract : This study aimed to compare the quality of human spermatozoa vitrified by direct plunging into liquid nitrogen vs. liquid air. Spermatozoa were divided into three groups: fresh spermatozoa (Group F) were used as a control. Spermatozoa suspension (20 μ l) was vitrified in open granules by direct dropping into liquid nitrogen (Group LN) or clean liquid air (Group LA). After warming at 37°C, the progressive motility rate of Group F was reduced from 65.9 ± 2.5% to 34.0 ± 1.9% (Group LN) and 38.1 ± 2.3% (Group LA), respectively (P1-2, 3 < 0.05). The reductions in viability were 65.6 ± 2.2%, 29.0 ± 1.8%, and 36.6 ± 2.6% for Groups F, LN, and LA, respectively (P1-2, 3 < 0.05). Comparing spermatozoa vitrified in liquid nitrogen vs. liquid air, no significant differences were detected in motility (34.0 ± 1.9% vs. 38.1 ± 2.3%), viability (29.0 ± 1.8% vs. 36.6 ± 2.6%), early apoptosis (13.8 ± 1.5% vs. 14.3 ± 1.8%), late apoptosis (45.5 ± 1.8% vs. 43.7 ± 2.2%), and necrosis (19.5 ± 2.0% vs. 15.0 ± 1.8%; p > 0.01 for all respective differences). There was a statistical tendency for increasing rates of "progressive motility" and "viability" and decreasing rates of "apoptosis" and "necrosis" when comparing spermatozoa vitrified in liquid air vs. liquid nitrogen. It is concluded that cryoprotectant-free vitrification by the direct dropping of human spermatozoa in a clean cooling agent (liquid air) is a good alternative to the use of nonsterile liquid nitrogen and can be used to cool cells while minimising the risk of microbial contamination.